Tax revenue and employment level in Nigeria - Titus, OKWU Andy; Peter, OGBEBOR I; Afokoghene, ATHORA Zion (The Economics and Finance Letters, 2025)
Employment levels are of concern in Nigeria, with unemployment and underemployment rates weakening the country’s economic performance and social order. The literature identifies employment levels among the key indicators of a country's economic health and agrees that the relationship between tax revenue (personal income tax, corporate income tax, value-added tax, petroleum profit tax) and employment levels is of interest to policymakers because taxation is critical in mobilizing funds for government investment. However, the effect of tax revenue on employment levels in Nigeria has remained contentious, as the available literature provides divergent views. Hence, this study examined the effect of tax revenues on employment levels in Nigeria, based on 43 years (1980–2023) of data sourced from the Central Bank of Nigeria and the World Bank. The study deployed the Autoregressive Distributed Lag (ARDL) model of econometric procedures. Tax revenue exerted inconsistent effects on employment levels in the short and long run. There is a mismatch between the country’s tax structure and current economic realities. Reforms should be implemented to align the tax structure with current economic conditions. Additionally, the economic environment should be assessed for effective future tax reforms, and existing tax-based project funding arrangements should be reviewed.